Misuse of open spaces according to park by laws - Ibrahim, Putri Haryati; Abu Bakar, Aniza; Zulkifli, Nabilah Huda (2017)
Parks are an example of open spaces where people can enjoy active and passive activities during free time to run away from the hustle and bustle of cities. Policies and guidelines have been implemented by the local authorities so that public parks and open spaces in their area of jurisdiction are convenient and safe for public use. This study aimed to identify and understand; the misuse of neighbourhood open spaces in the area of Majlis Bandaraya Petaling Jaya (MBPJ) jurisdiction according to the Park Bylaws (MBPJ 2005). Six (6) open spaces were chosen namely; Taman Jaya in Section 10, Taman Aman in Section 22 and several neighbourhood open spaces located at Section 13, Section 14, Section 17, Section 19. The methodologies used were questionnaire survey that obtained a sample size of 90 respondents and in-depth interview session with the officers from the Landscape Department of MBPJ. This study found that illegal dumping, vandalism and loitering were the main offences that occur in the neighbourhood open spaces while illegal parking, walking the dogs in the parks and hawking were found to be example of minor offences. This study noticed that violation of park bylaws occurred mainly due to the lack of awareness and public involvement. The study also outlined several suggestions to address the issues encountered in order to reduce problems regarding the misuse of open spaces that perhaps can leads to the betterment usage of the areas.